Drug Logistics Management in The Pharmaceutical Service Unit of The Pangkep District Health Service - Adawiyah Arifin, Ince Annisah; Syamsinar Jamal; Mutmainnah (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2024)
The Pharmaceutical Services Unit is responsible for managing health supplies which includes planning, procurement, storage and distribution of drug logistics. This research aims to obtain an overview of drug logistics management in the Pharmaceutical Services Unit of the Pangkep District Health Service. This study uses a qualitative method with an inductive approach. The research subjects were divided into key informants, namely the head of the pharmaceutical installation and ordinary informants, namely employees of the pharmaceutical service unit. The management of drug logistics carried out by the service unit forming the Pangkep District Health Service is not optimal because the planning for drug needs is only based on the consumption method, namely planning drug needs based on data on drug needs at each Puskesmas in the previous year and is not optimal in providing drug storage space due to the narrow storage warehouse. The management of drug logistics carried out by the pharmaceutical service unit of the Pangkep District Health Service has not been optimal in the areas of planning drug needs and drug storage.